Drip, Ship, and Grip, then Slice and Dice: Comprehensive Stroke Center Management of Cervical and Intracranial Emboli - Hinman, Jason D.; Rao, Neal M.; Yallapragada, Anil; Capri, Joe; Souda, Puneet; Whitelegge, Julian P.; Yong, William H.; Jahan, Reza; Quinones-Baldrich, William; Saver, Jeffrey L. (Frontiers in Neurology, 2013)
BACKGROUND AND PURPOSE: Tandem acute thrombotic emboli in the cervical and intracranial arteries are an unusual case of stroke presenting unique management challenges. In regional systems of acute stroke care anchored by Comprehensive Stroke Centers, combined fibrinolytic, endovascular, and open surgical intervention is a new therapeutic option. SUMMARY OF CASE: A 28 year old male underwent retinal surgery, including post-operative neck compression and the next day presented to a primary stroke center with aphasia and right hemiplegia. Intravenous tissue plasminogen activator therapy was initiated and the patient was transferred to a comprehensive stroke center (CSC) for higher level of care (drip and ship). Imaging at the CSC demonstrated tandem thrombi: a near occlusive lesion at the origin of the left cervical internal carotid artery and a total occlusion of the M1 segment of the left middle cerebral artery. Endovascular thrombectomy with the Solitaire stent retriever resulted in intracranial recanalization (grip). Immediately after the endovascular procedure, open carotid thrombectomy was performed to achieve cervical carotid revascularization without systemic heparinization (slice). Both cervical carotid and intracranial thrombi were processed for proteomic analysis via mass spectrometry (dice). CONCLUSION: Combined fibrinolytic, endovascular, and open surgical intervention can yield revascularization and good clinical outcome in cases of tandem lesions.